ANALISIS PUTUSAN HAKIM DALAM KASUS PEMBUNUHAN DI UARAU, KABUPATEN MALAKA - Samara, Finsensius; Rambu Nuning, Kinanti; Leni Cermeta, Amelia; Ola Ama, Fransiskus; Huki Haba, Apriyanto; Mbale , Yohanes (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This Examination Report (BAP) contains the testimony of witness Y.M. regarding the murder case of R.I which occurred in the Wekamanasa forest, Malaka Regency. The witness stated that he found the victim dead with a slash wound on the neck. The witness also saw F.T.K Alias F at the scene holding a machete and immediately ran away from the scene. The witness knew F and stated that he had seen F carrying the victim's machete. Based on the witness's testimony, F. is strongly suspected of being the perpetrator of the murder of R.I. The motive for the murder is strongly suspected to be revenge due to accusations of cattle theft made by R.I. against F.T.K.